Recent Excavations and Discoveries - Fischer, Anders; Madsen, Bo; Holm, J.; Petersen, E. Brinch; Petersen, Peter Vang; Skaarup, Jørgen; Nielsen, P. O. (Journal of Danish Archaeology, 1982)
Recent Excavations and Discoveries